Penerapan Cadangan Kerugian Penurunan Nilai, Pendapatan Murabahah Dan Kinerja Keuangan Pada Bank Umum Syariah Tahun 2014 - Muji Suhartini; Saiful Anwar (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2016)
Provision Impairment Loss (CKPN) is allowance for value assets after there is an impairment less than the beginning balance. The calculation of CKPN is divided into two methods, they are individual and collective. The researcher used analysis as instrument of the research, that was structural equation modeling (SEM). The research was examined the effect of CKPN to Murabahah Income and Financial Performance that consists of four variables, they are NIM/NCOM, NPF, ROE, and ROA. The researcher used the data from 11 General Syariah Bank in 2014. The researcher used SEM method with alternative Partial Least Square (PLS) and used SmartPLS 1.0 application. The result showed that CKPN was effected for the level of Murabahah Income and Financial Performance at General Syariah Bank in 2014. The statistical result of the first hypnotical test was 0,951 with T-Statistic 55,884, it meant that those number was more than T-Table 2.326 or in other words Hypothesis 1 (H1) was accepted. The result of second hypnotical was 0,689 with T-Statistic 25,687 and more than T-Table 2.326 or in other words Hypothesis 2 (H2) was accepted.